Relationship between expression of human gingival beta‐defensins and levels of periodontopathogens in subgingival plaque. (12th May 2014) - Wang, P.; Duan, D.; Zhou, X.; Li, X.; Yang, J.; Deng, M.; Xu, Y.
<x xml:space="preserve">Abstract</x> Background and Objective Human beta‐defensins (hBDs) are a group of antimicrobial peptides important in epithelial innate immunity, and their differential expression is associated with periodontal diseases. The aim of this study was to explore relationships among hBDs, total subgingival bacteria and periodontopathogens in healthy subjects and in patients with chronic periodontitis. Material and Methods The periodontal clinical parameters of 29 healthy subjects and 25 patients with chronic periodontitis were recorded. The relative expression of hBD1, hBD2 and hBD3 genes in gingival biopsies was measured using real‐time PCR. The numbers of total bacteria and of Treponema denticola, Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Fusobacterium nucleatum and Tannerella forsythia in subgingival plaque were quantified by real‐time PCR. Data were analyzed using the Mann–Whitney U‐test and Spearman's rank correlation test. Results No significant differences in expression of the hBD genes were found between the group of healthy subjects and the group of patients with chronic periodontitis. Total bacteria and T. denticola were detected in all participants. F. nucleatum and T. forsythia were detected in all patients with chronic periodontitis and in 86.21% and 51.72%, respectively, of healthy volunteers. P. gingivalis and A. actinomycetemcomitans were detected in 24.14% and 17.24%, respectively, of the healthy group and in 84.00% and 12.00%, respectively, of the chronic periodontitis group. The prevalence of all bacteria, except A. actinomycetemcomitans, was significantly higher in the group of patients with chronic periodontitis than in the group of healthy subjects (p < 0.05). A significant, negative correlation was observed between total bacteria and hBD‐2 (r = −0.384, p = 0.011). Upon analyzing the data in different groups, total bacteria and hBD‐2 were significantly correlated (r = −0.492, p = 0.026) only in the group of healthy subjects. Conclusion The negative correlations between hBD‐2 and total bacteria, especially in the group of healthy subjects, indicate that hBDs may play an important role by limiting an increase of bacterial load at the initial stage of periodontitis.